2021
DOI: 10.1016/j.cub.2021.09.013
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampus constructs narrative memories across distant events

Abstract: The hippocampus constructs narrative memories across distant events Highlights d In real life, people use a single narrative to remember multiple, separated events d Activity in the hippocampus can bridge separate events to form a coherent narrative d Activity in the hippocampus preferentially supports recall of coherent narratives d The hippocampus may support a narrative architecture for real-life memory

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 87 publications
6
59
0
Order By: Relevance
“…Patterns of hippocampal activity, including activity at event boundaries, were more similar between distant events that formed one cohesive narrative during encoding of fictional stories compared with overlapping events from unrelated narratives. One day later, the hippocampus preferentially supported detailed recall of coherent narrative events, through reinstatement of hippocampal activity patterns from encoding [92]. Remarkably, during EMDR protocol, patients may start processing an event related to a NC and then recall events that are temporally very distant and that may be related to NC but also to PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of hippocampal activity, including activity at event boundaries, were more similar between distant events that formed one cohesive narrative during encoding of fictional stories compared with overlapping events from unrelated narratives. One day later, the hippocampus preferentially supported detailed recall of coherent narrative events, through reinstatement of hippocampal activity patterns from encoding [92]. Remarkably, during EMDR protocol, patients may start processing an event related to a NC and then recall events that are temporally very distant and that may be related to NC but also to PC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that narrative memories are constructed by the hippocampus across distant events [92]. Patterns of hippocampal activity, including activity at event boundaries, were more similar between distant events that formed one cohesive narrative during encoding of fictional stories compared with overlapping events from unrelated narratives.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-event connections may also benefit encoding. During movie watching, events highly connected with other events are more likely to reactivate and be reactivated by the other events containing shared components 43,47,48 . Consistent with this, we found that the coupling between the hippocampus and a cortical region involved in representing events (PMC 16,49 , see below) was stronger when subjects were watching events with higher semantic centrality.…”
Section: Discussionmentioning
confidence: 99%
“…The method of the HeNReG is based on the presupposition that creating a mental landscape of what is considered true by participants, in relation to what they value with respect to health, is the optimal way to construct a robust narrative [59]. The reason for this assumption is that narratives are formed and accessed in the hippocampus [60]. As such, this stops the creation of memories resulting from fear created in the amygdala or traumatic memory formation in the hippocampus elicited from burnout [61].…”
Section: Analysis Of the Methodsmentioning
confidence: 99%